2017
DOI: 10.1111/dme.13384
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events associated with second‐line anti‐diabetes treatments: analysis of real‐world Korean data

Abstract: Analysis of Korea National Health Insurance database showed that MET + DPP4i treatment for diabetes had a lower CVD risk than MET + SU treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Also, they report an elevated risk for add‐on sulfonylureas compared with add‐on thiazolidinediones (specifically pioglitazone). Similar findings have been found from data from other healthcare systems, such as the Taiwan National Health Insurance Database , the Swedish National Diabetes Registry and the Korean National Health Insurance Database .…”
Section: Discussionsupporting
confidence: 87%
“…Also, they report an elevated risk for add‐on sulfonylureas compared with add‐on thiazolidinediones (specifically pioglitazone). Similar findings have been found from data from other healthcare systems, such as the Taiwan National Health Insurance Database , the Swedish National Diabetes Registry and the Korean National Health Insurance Database .…”
Section: Discussionsupporting
confidence: 87%
“…Zghebi et al found that TZD as an add-on medication to metformin was associated with lower risk of major cardiovascular disease or death, when compared with a SU add-on treatment to metformin in an UK Clinical Practice Research Datalink [ 26 ]. Recently, a Korean Health Insurance Service Study showed that TZD as a second-line drug to metformin had relatively lower risk of CVD compared to SU, although these findings did not reach statistical significance [ 20 ]. Similar to these previous studies, we observed that both TZD and AGI as the second-line ADAs added to metformin were associated with decreased cardiovascular risk including death, stroke and ACS, although the comparators were different [ 18 , 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean Health Insurance Review and Assessment Database Study, TZD (pioglitazone) added to metformin was associated with a decreased total CVD risk in patients with T2DM [ 19 ]. Another Korean Health Insurance Database Study showed that DPP-4I added to metformin had a lower CVD risk than SU added to metformin in T2DM patients [ 20 ]. However, Chang et al using a Taiwan Diabetic Database, found that there were no differences in cardiovascular risk among several different add-on second-line oral ADAs, in a newly diagnosed diabetic population [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that DPP-4i as a monotherapy or in combination with other oral hypoglycemic agents has potentially beneficial effects on cardiovascular outcomes. 3) 4) 5) 6) A recent study by Ha et al, 6) based on the 2011–2015 Korean National Health Insurance Service (NHIS) database, reported that people with type 2 diabetes who added a DPP-4i as a second-line drug to metformin had lower risks of cardiovascular disease (CVD) and all-cause mortality, compared to those who added sulfonylurea. However, there are some practical differences between the DPP-4is such as duration of action, metabolism, elimination, and isolated compound-specific characteristics.…”
Section: Introductionmentioning
confidence: 99%